The Effect of REFIT on Irish Wholesale Electricity Prices - Devitt, Conor; Malaguzzi Valeri, Laura (Economic & Social Studies, 2011)
This paper evaluates the likely effect of REFIT, the Irish scheme to support renewable electricity generation, on the wholesale price of electricity. The cost of REFIT is passed on to Irish consumers. Here we calculate that, when there are 4,071MW of on-shore wind in the Republic of Ireland, the cost of the REFIT scheme is between 5 per cent and 10 per cent of the gross wholesale price of electricity. Off-shore wind has higher levels of support than on-shore wind, as do technologies that are still in development such as wave and tidal. When off-shore wind, wave and tidal are added to the system, the cost of REFIT increases significantly. We argue that wave and tidal should be sustained with a different scheme that provides capital grants, and that off-shore wind that is channelled to exports should not be supported by Irish consumers.
Keywords: electricity pricing; energy; Ireland